Mozambique : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1997)
This paper reviews economic developments in the Republic of Mozambique during 1990-96. Under the Economic and Social Rehabilitation Program (ESRP), the economy has made impressive economic gains. Real GDP growth averaged 6.7 percent in 1987-95, despite the civil war, a decline in the terms of trade, and natural disasters. Investment and export volumes are growing rapidly. These achievements have been capped in the last two years (1995-96) by a dramatic decline in inflation-from 70 percent in 1994 to 13 percent in the first eight months of 1996.